The length of the rope is 60 feet.
Given that, a flagpole is 53 feet tall. A rope is tied to the top of the flagpole and secured to the ground 28 feet from the base of the flagpole.
The Pythagoras theorem which is also referred to as the Pythagoreantheorem explains the relationship between the three sides of a right-angled triangle. According to the Pythagoras theorem, the square of the hypotenuse is equal to the sum of the squares of the other two sides of a triangle.
Let the length of the rope be x.
Now, x²=53²+28²
⇒x²=2,809+784
⇒x=59.94≈60
Therefore, the length of the rope is 60 feet.
To learn more about the Pythagoras theorem visit:
brainly.com/question/21926466.
#SPJ2
StartFraction 13 Over 3 EndFraction
9
27
Answer:
its c
Step-by-step explanation:
i took the test and got 100
Answer: 3/9 i think
Step-by-step explanation:
The calculated fraction 47/10 to a mixed number is 4 7/10
From the question, we have the following parameters that can be used in our computation:
Number = 47/10
Convert to a fraction
Number = 47/10
Divide 47 by 10
So, we have
Quotient = 4
Next, we have
Remainder = 47 - 4 * 10
Evaluate the products
Remainder = 7
So, we have
Fraction = 4 7/10
Simplify
Fraction = 4 7/10
Hence, the fraction to a mixed number is 4 7/10
Read more about fraction at
#SPJ6
(x^2+3)(4x−5)
5x^2(x+4)(3x−5)
5x(x^2+3)(4x−5)
5x(x^2−3)(4x+5)
The expression correctly shows 20x⁴-25x³+60x²-75x will be 5x(x²+3)(4x-5).Option C is correct.
An equation is a statement that two expressions, which include variables and/or numbers, are equal. In essence, equations are questions, and efforts to systematically find solutions to these questions have been the driving forces behind the creation of mathematics.
It is given that,
The expression is,
=20x⁴-25x³+60x²-75x
Take 5x³ from the first two terms and 15x from the third and fourth terms as
=20x⁴-25x³+60x²-75x
=5x³(4x-5) + 15x(4x-5)
=(5x³+15x)(4x-5)
Thus, the expression correctly shows 20x⁴-25x³+60x²-75x will be 5x(x²+3)(4x-5). Option C is correct.
Learn more about the equation here,
#SPJ2
Step-by-step explanation:
The third option: 5x(x^2+3)(4x-5)
because FOIL first, inner, outter, last
The two parentheses become (4x^3-5x^2+12x)
then 5x outside multiplys that whole parentheses. To get your correct expression